2006
DOI: 10.1182/blood-2005-02-0581
|View full text |Cite
|
Sign up to set email alerts
|

Reduced retention of radioprotective hematopoietic cells within the bone marrow microenvironment in CXCR4–/– chimeric mice

Abstract: The physiologic role of CXCR4 on hematopoietic stem/progenitor cells (HSPCs) is not fully understood. Here, we show that radioprotection of lethally irradiated mice by embryonic day 14.5 (E14.5) CXCR4 ؊/؊ fetal liver (FL) cells was markedly impaired when compared with CXCR4 ؉/؉ counterparts, but this defect was rescued when hosts were engrafted with high cell numbers. This quantitative defect contrasted with a similar content in hematopoietic colony-forming cells (CFCs), splenic colony-forming units (CFUs-S), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
95
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 57 publications
(101 reference statements)
10
95
0
2
Order By: Relevance
“…Although some recent studies have questioned the role of CXCR4 in HSC homing in fetal liver hematopoiesis [31] and CXCR4-overexpression studies [32], it is commonly accepted that the CXCR4/CXCL12 axis plays a significant role in the BM homing of transplanted HSPCs [33,34]. Consistent with the role of CXCR4 in HSC homing, we observed that b7KO HSCs were impaired in their ability to migrate toward CXCL12 in vitro and home to BM in vivo (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Although some recent studies have questioned the role of CXCR4 in HSC homing in fetal liver hematopoiesis [31] and CXCR4-overexpression studies [32], it is commonly accepted that the CXCR4/CXCL12 axis plays a significant role in the BM homing of transplanted HSPCs [33,34]. Consistent with the role of CXCR4 in HSC homing, we observed that b7KO HSCs were impaired in their ability to migrate toward CXCL12 in vitro and home to BM in vivo (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Alternatively, it may be that a homing assay performed with total liver cells reveals a constitutive promigratory function of PTK7, in contrast to long-term engraftment reflecting BM microenvironmental signaling through PTK7 in HSCs. Similar complex mechanisms of cell cycle regulation and differential homing of mature cells versus HSPCs homing to the BM were also attributed to CXCR4 (51)(52)(53)(54). Whether PTK7 and CXCR4 signaling share more in common remains to be addressed.…”
Section: Discussionmentioning
confidence: 92%
“…Early transplantation experiments demonstrated that primitive hematopoietic cells required CXCR4 and CXCL12 interaction for effi cient engraftment ( 12,18 ). Later studies involved transplantation of CXCR4-inactivated primitive hematopoietic cells into irradiated hosts, and showed that the recovery of these cells in the BM within 24 h was quantitatively normal compared with that of WT cells ( 13,19 ). These results imply that early BM homing of primitive hematopoietic cells might be CXCR4 independent, but BM retention of these cells requires CXCR4.…”
Section: Brief Definitive Reportmentioning
confidence: 90%